1991
DOI: 10.1038/bjc.1991.282
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P-glycoprotein restricted to normal cells in neuroblastoma biopsies

Abstract: Summary Immunohistological detection of P-glycoprotein (P-gp) with monoclonal antibody C219 was performed on serial sections of 37 neuroblastoma specimens representative of the different forms of the disease, from stage 1 ganglioneuroma to stage 4 neuroblastoma. Malignant cells, irrespective of their degree of maturation varying from neuroblasts to ganglion cells, were negative on all specimens. The expression of P-glycoprotein was detected in nine specimens, but it was restricted to normal cells within the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, in clinical NB studies, conflicting reports exist regarding the prognostic value of MDR1 expression (Goldstein et al, 1990;Chan et al, 1991;Norris et al, 1996). Although P-glycoprotein expression was reported to be a predictor of outcome of therapy for NB patients in some studies (Goldstein et al, 1990;Chan et al, 1991), other series have failed to show any correlation (Favrot et al, 1991;Norris et al, 1996). In one study, high levels of MDR1 expression were found to be predictive of outcome only in older children with NB tumors that lacked MYCN amplification .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in clinical NB studies, conflicting reports exist regarding the prognostic value of MDR1 expression (Goldstein et al, 1990;Chan et al, 1991;Norris et al, 1996). Although P-glycoprotein expression was reported to be a predictor of outcome of therapy for NB patients in some studies (Goldstein et al, 1990;Chan et al, 1991), other series have failed to show any correlation (Favrot et al, 1991;Norris et al, 1996). In one study, high levels of MDR1 expression were found to be predictive of outcome only in older children with NB tumors that lacked MYCN amplification .…”
Section: Discussionmentioning
confidence: 94%
“…In one study, high levels of MDR1 expression were found to be predictive of outcome only in older children with NB tumors that lacked MYCN amplification . Furthermore, in contrast to MRP1, the level of expression of MDR1 is lower in tumors with MYCN amplification compared to those without amplification (Nakagawara et al, 1990;Favrot et al, 1991;Norris et al, 1996). Thus, the contribution, if any, of MDR1 expression to the drugresistant phenotype of MYCN-amplified NB tumors remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In sarcoma of childhood and neuroblastoma, expression of P-glycoprotein determined with the monoclonal antibody C219 was found to be an important prognostic factor (Chan et al, 1991;. Another group using the same monoclonal antibody found that P-glycoprotein expression was restricted to normal cells in neuroblastoma biopsies (Favrot et al, 1991). In P-glycoprotein positive resistant multiple myeloma verapamil has been shown to increase the effect of vincristine, doxorubicin and prednisone chemotherapy in some but not all patients (Salmon et al, 1991 The patients were treated between 1982 and 1991 and received combination chemotherapy according to different protocols.…”
mentioning
confidence: 96%
“…The disparity and variability in published reports may be due to the many different methods used for analysis of Pgp [15][16][17][18][19][20][21][22][23][24] or MDR1 expression [25][26][27][28][29][30][31] in tumor specimens. Pgp expression has been measured using different immunodetection techniques (Western blot, immunohistochemistry and flow cytometry).…”
Section: P-glycoprotein-mediated Multidrug Resistancementioning
confidence: 99%
“…These investigators suggested that Pgp expression may be predictive of outcome in nonlocalized neuroblastoma. In another report of 37 cases (22 specimens obtained after treatment and 15 obtained at diagnosis) by Favrot and coworkers, Pgp was analyzed using immunohistochemistry with mAb C219 and no detectable staining was noted in malignant cells in all of these specimens [18]. However, these investigators noted immunostaining of the stromal cell component 9 of the 37 specimens.…”
Section: P-glycoprotein Expression In Solid Tumorsmentioning
confidence: 99%